2007
DOI: 10.1063/1.2424429
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of double layers in expanding plasmas

Abstract: Double layers (DLs) have been observed in a plasma reactor composed of a source chamber attached to a larger expanding chamber. Positive ion beams generated across the DL were characterized in the low plasma potential region using retarding field energy analyzers. In electropositive gases, DLs were formed at very low pressures (between 0.1 and 1 mTorr) with the plasma expansion forced by a strongly diverging magnetic field. The DL remains static, robust to changes in boundary conditions, and its position is re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 65 publications
(131 reference statements)
8
83
0
Order By: Relevance
“…case 1A refers to setup 1, configuration A. Case 1A will be used to reproduce prior works 11,14,16,12,13,15,17 , since the MFG is located close to the diameter change. Case 2B is quiet similar to case 1A, therefore, it is possible to study the influence of the distance to the source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…case 1A refers to setup 1, configuration A. Case 1A will be used to reproduce prior works 11,14,16,12,13,15,17 , since the MFG is located close to the diameter change. Case 2B is quiet similar to case 1A, therefore, it is possible to study the influence of the distance to the source.…”
Section: Methodsmentioning
confidence: 99%
“…However, DLs observed in space plasmas are usually current free. Although, a number of theoretical 7,8,9 and experimental 10,11,12,13,14,15,16,17 studies of these current-free DLs have been performed in the last decade, the exact formation mechanism is still under debate 18 . Nevertheless, applications such as ion thrusters 19,20,21 are already under development.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments and theories have shown the DL formation and/or the ion acceleration in expanding plasmas. [3][4][5][6][7][8][9][10] Charles and Boswell have suggested that the new type of electric thruster, named the helicon double layer thruster, can yield a long-lifetime because it does not require ion extraction electrodes. Recent measurements of the electron energy distribution function upstream of the helicon double layer showed that only a single upstream plasma source is required to maintain the formation of the double layer, 10,11 hence the above-mentioned ion accelerator is considered to be applicable to the thruster.…”
mentioning
confidence: 99%
“…While the first scheme could be obtained with only one plasma source, the second one requires two independent sources. Note that in this configuration, axial flows could be driven from the magnetic expansion of the plasma (Charles and Boswell 2004;Plihon et al 2007). Alternative schemes such as single grid acceleration of the plasma (Dudin and Rafalskyi 2009) may also be implemented to independently control the ratio of the poloidal (s) and toroidal (t) flows.…”
Section: Machine Description and Capabilitiesmentioning
confidence: 99%